Management of Natura 2000 sites in Poland in the context of sustainable development – current challenges and conflicts - Cent, Joanna; Grodzińska-Jurczak, Małgorzata; Pietrzyk-Kaszyńska, Agata; Gutowska, Justyna (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
Abstract: The sustainable development of rural areas could be based on multifunctional characteristics of locality according to various values, including natural and biological values. Areas with high values are often included in conservation programmes and the network of protected areas, such as Natura 2000. Very often these values are perceived as obstacles rather than opportunities for local development. In the case of Natura 2000, there have been a number of social conflicts in recent years hindering not only the effectiveness of management practices (i.e. conservation of endangered species and habitats), but also making it difficult to benefit socially and economically from these sites. This paper presents the results of research on the current problems and challenges related to the level of acceptance and opinions of Natura 2000 of a key stakeholders’ group. It indentifies the main barriers and chances perceived by the stakeholders at a preparation phase for management plans for Natura 2000 sites. The study was conducted with 350 participants of workshops organised within the Natura Mission – LIFE+ program in all Polish voivodships between January and March 2013. The results show that although respondents perceive Natura 2000 as potentially enhancing local development (mostly in respect to ecotourism sector), they still identify barriers stemming from Natura 2000 implementation that result in a negative attitude of local communities. Respondents also suggested the need for wider public participation in the setting up of management plans. If the management of Natura 2000 is to support local development, there is a need for better education about the programme, more engagement of local stakeholders and better economic support for the groups whose activities and wellbeing are affected by the protected areas.
Keywords: Natura 2000; public participation; management plans; nature conservation; sustainable development